MARKETING REVOLUTION THROUGH INNOVATION: DEVELOPINGADAPTIVE STRATEGIES TO ADDRESS CHANGING MARKET DYNAMICS: A LITERATURE REVIEW ON MARKETING MANAGEMENT AND CONSUMER THEORIES - Nooraisyah; Nina Triolita; Muhamad Risal Tawil (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
In the fast-paced landscape of modern business, traditional marketing strategies are being challenged by dynamic market dynamics, technological advancements, and shifting consumer behaviors. This literature review explores the transformative potential of innovation and adaptive strategies in revolutionizing marketing practices. Drawing on an extensive array of marketing management and consumer theories, the review examines the evolution of marketing paradigms toward customer-centric approaches, the significance of innovation in driving competitiveness, and the importance of understanding consumer behavior for effective strategy formulation. Furthermore, it delves into adaptive strategies tailored to navigate the complexities of dynamic markets, emphasizing agility, diversification, and data-driven decision-making. Additionally, the review highlights the pivotal role of digital transformation in enhancing organizational agility, streamlining operations, and fostering innovation. Through a synthesis of these key findings, the review provides insights for businesses seeking to stay competitive and relevant in today's ever-changing marketplace. Overall, it underscores the necessity for organizations to embrace innovation and adaptive strategies to address the challenges posed by changing market dynamics, thereby paving the way for sustained growth and success.